Penerimaan Pengguna Instagram terhadap Analogi Visual Seksualitas dengan Makanan oleh Influencer Instagram - Intan Rigita Rizki Fauzia (Airlangga University, 2020)
This research focuses on the acceptance of Instagram users to the visual analogy of sexualitywith food by Instagram influencers when delivering sex education material that is stillconsidered taboo in Indonesia. By using a qualitative approach and a type of descriptiveresearch, this research focuses on the meaning received by the nine informants who haveparticipated. The research method used is Reception Analysis with in-depth interviews as datacollection technique. The literature review used is a visual analogy to explain the taboo aboutsexuality, sexuality in Indonesia, problems of formal sex education, symbolic construction ofsexuality in traditional media, and sexuality content that appears on Instagram social media.The findings of this study indicate that the informants interpret the visual analogy of sexualitybased on the concept of heteronormativity in everyday life. Then, stereotypes about sexualitythat develop in the community also become a reference when they answer questions. Theperception of the state of Indonesia as homophobic and transphobic country, but when facedwith a visual analogy in the form of food, the informants did not object to the existence ofLGBT groups or to the concept of homosexuality